The Influence of Disaster Education on the Ability of Aceh Muhammadiyah STIKes Students in Managing Risks - Hayati Hayati; Wirda Wirda; Ani Darliani; Erly Muavizar; Siti Rozaina Kamsani (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Aceh Province, as a region with a long history of disasters, requires higher education institutions, especially in the health sector, to prepare graduates who are competent in disaster risk management. This research aims to examine the influence of disaster education on the ability of STIKes Muhammadiyah Aceh students to manage disaster risks. This research employs a quantitative approach through a quasi-experimental design with a pretest-posttest control group design. Data was collected using a 35-item questionnaire instrument that measures three dimensions, namely knowledge, attitudes and practical skills in disaster risk management. The validity of the instrument was tested using the pearson product-moment correlation with a threshold of r ≥ 0.30, while the reliability was tested using cronbach's alpha with a value of 0.871, which indicates a high level of reliability. Hypothesis testing was carried out using the paired sample t-test. The research results showed a significant increase in student knowledge scores, from a pretest average of 43.19 to 53.12 on the posttest, with a difference of 9.93 points. The significance value p = 0.000 (p < 0.05) confirms that H₀ is rejected and H₁ is accepted. This research concludes that disaster education has a significant effect on improving the knowledge of STIKes Muhammadiyah Aceh students in managing disaster risks. The integration of disaster education into the curriculum through interactive learning, simulations and cross-sector collaboration is highly recommended to strengthen students' preparedness as prospective health professionals